Matter effects in neutrino visible decay at future long-baseline experiments - Ascencio-Sosa M.V. (2018)
A.M.G. and J.J.P. acknowledge funding by the Dirección de Gestión de la Investigación at PUCP, through grant DGI-2015-3-0026. M.V.A.S. acknowledges funding by CienciActiva-CONCYTEC Grants 026-2015 and CONV-236-2015-FONDECYT. A.M.C.C. received funding from CienciActiva-CONCYTEC Grant 233-2015-1. We would like to thank F. Díaz-Desposorio for his help with the GLoBES implementation, and O. A. Díaz in the Dirección de Tecnologías de Información for support within the LEGION system.